Targeting of Uropathogenic Escherichia coli papG gene using CRISPR-dot nanocomplex reduced virulence of UPEC - Surbhi Gupta (Nature Portfolio, 2021)
Abstract Urinary tract infections (UTI) are the most common infectious diseases in the world. It is becoming increasingly tough to treat because of emergence of antibiotic resistance. So, there is an exigency to develop novel anti-virulence therapeutics to combat multi-drug resistance pathogenic strains. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) discovery has revolutionized the gene editing technology for targeted approach. The greatest obstacle for CRISPR/Cas9 is cargo delivery systems and both viral and plasmid methods have disadvantages. Here, we report a highly efficient novel CRISPR based gene editing strategy, CRISPR-dots for targeting virulence factor Fimbrial Adhesion (papG gene), the bacterial adhesion molecule. Carbon quantum dots (CQD) were used as a delivery vehicle for Cas9 and gRNA into CFT073, a UPEC strain. CQDs were covalently conjugated to cas9 and papG-targeted guide RNA (gRNA) forming a nanocomplex CRISPR-dots (Cri-dots) as confirmed by DLS and transmission electron microscopy. Cri-dots-papG significantly targeted papG as demonstrated by decrease in the expression of papG.Further papG deficient UPEC had significantly reduced adherence ability and biofilm forming ability as demonstrated by fluorescence microscopy and scanning electron microscopy. Also, papG deficient UPEC had reduced virulence as shown by significantly increased survival of Caenorhabditis elegans (C. elegans) worms compared to UPEC. Our findings suggest that targeting of papG gene using Cri-dots nanocomplexes significantly reduced the pathogenicity of UPEC. Thus, Cri-dots nanocomplex offer a novel anti-bacterial strategy against multi-drug resistant UPEC.